2008
DOI: 10.4049/jimmunol.181.2.1232
|View full text |Cite
|
Sign up to set email alerts
|

Osteal Tissue Macrophages Are Intercalated throughout Human and Mouse Bone Lining Tissues and Regulate Osteoblast Function In Vitro and In Vivo

Abstract: Resident macrophages are an integral component of many tissues and are important in homeostasis and repair. This study examines the contribution of resident tissue macrophages to bone physiology. Using immunohistochemistry, we showed that a discrete population of resident macrophages, OsteoMacs, was intercalated throughout murine and human osteal tissues. OsteoMacs were distributed among other bone lining cells within both endosteum and periosteum. Furthermore, OsteoMacs were coisolated with osteoblasts in mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
663
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 618 publications
(699 citation statements)
references
References 59 publications
35
663
0
1
Order By: Relevance
“…Activated macrophages secrete BMP2 and transforming growth factor b (TGF-b). It has been shown that the discharging macrophages result in the inhibition of in vivo bone formation [65][66][67][68]. Thereby, magnesium scaffolds coated with -TCP showed desired osteogenesis over osteoclastogenesis, due to the upregulation of osteoinductive molecules secreted by macrophages in contact with -TCP coating [63].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Activated macrophages secrete BMP2 and transforming growth factor b (TGF-b). It has been shown that the discharging macrophages result in the inhibition of in vivo bone formation [65][66][67][68]. Thereby, magnesium scaffolds coated with -TCP showed desired osteogenesis over osteoclastogenesis, due to the upregulation of osteoinductive molecules secreted by macrophages in contact with -TCP coating [63].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Immunohistochemistry was used to examine expression of F4/80 (rat anti-mouse F4/80, clone CI:A3-1, AbD Serotec, Oxford, UK) and osteocalcin (rabbit anti-mouse osteocalcin, Alexis Biochemicals, San Diego, CA, USA) as previously described. 13,23 Flow cytometry…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…11,13,14 Once these endosteal niches are shutdown, HSC mobilization is initiated and possibly further amplified by protease-dependant mechanisms 13 involving neutrophil proteases, 15 CD26, 16 activation of the complement cascade 17 --19 and the thrombolytic pathway. 20 It has recently been reported that specific populations of BM macrophages are necessary to maintain the function of HSC niches in the BM and for the mobilizing effect of G-CSF 13,21,22 in particular osteoblast-supportive endosteal phagocytic macrophages called osteomacs 13,23 and CD11b þ F4/80 þ Ly-6G þ phagocytic macrophages expressing CD169, which are in close association with MSC. 13,21 Whether these two macrophage populations are distinct according to niche location or functionally overlap remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…They were present in resting osteal tissues and were increased at sites undergoing active bone anabolism. [12][13][14] Osteomacs have pivotal roles in bone and BM homeostasis through the support of osteoblast maintenance and functional activity. 13,15 In mice, osteomacs expressed numerous myeloid lineage markers including but not limited to F4/80, CD115, Mac-3 and CD68 ( Figure 2 and refs 12,13 and unpublished data).…”
Section: Resident Tissue Macrophages and Osteomacsmentioning
confidence: 99%